Insulating coating for aluminum alloy optical component and preparation method of insulating coating

By using anodized electrolyte with zero sulfur content on the aluminum alloy optical module to form an insulating coating and sealing holes in the target solution, the problem of poor performance of the existing insulating coating is solved and higher optical Performance and corrosion resistance.

CN119491283APending Publication Date: 2025-02-21XIAN RARE METAL MATERIALS RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411672502.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The performance of existing aluminum alloy optical components is poor, and sulfur elements weaken the optical characteristics, corrosion resistance and thermal stability of the film layer, affect the imaging quality and service life, and it is difficult to ensure dimensional accuracy.

Method used

Anodic electrolyte with zero sulfur content was used for oxidation electrolytic treatment to form an intermediate insulating coating, and a silane coupling agent and methanol were included in the target solution for sealing to form a target insulating coating.

Benefits of technology

It improves light transmittance and reflectivity, improves imaging clarity and brightness, enhances corrosion resistance and service life, and ensures stable operation in different environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119491283A_ABST
    Figure CN119491283A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of an insulating coating for an aluminum alloy optical assembly and the insulating coating for the aluminum alloy optical assembly, and relates to the technical field of coating treatment. The preparation method comprises the steps that a to-be-treated aluminum alloy optical assembly is pretreated to obtain a clean aluminum alloy assembly; the clean aluminum alloy assembly is placed in an anodic oxidation electrolyte, and an intermediate insulating coating is formed on the surface of the clean aluminum alloy assembly through oxidation electrolysis treatment; wherein the sulfur content of the anodic oxidation electrolyte is zero; the aluminum alloy assembly with the middle insulating coating formed on the surface is placed in a target solution for hole sealing, so that a target insulating coating is formed on the surface of the aluminum alloy assembly; wherein the target solution contains a silane coupling agent and methanol. The performance of the insulating coating for the aluminum alloy optical assembly can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of coating treatment, and in particular to a method for preparing an insulating coating for an aluminum alloy optical component and an insulating coating for the aluminum alloy optical component. Background Art

[0002] Optical systems are widely used in aerospace technology, military security, information transmission and industrial automation. At present, lightweight, low cost, high efficiency, high resolution and long life have become the development direction of optical systems. Aluminum alloy, as a lightweight, high-strength and corrosion-resistant material, is widely used in the manufacture of optical components because it is easy to move, install and operate optical systems.

[0003] Modern optical systems often need to work with electronic devices. During service, there are electrostatic damage, electromagnetic interference, and thermal deformation caused by current conduction, which cause irreversible damage to optical components and affect the optical performance stability and service life of optical components. By insulating the surface of optical components, it is possible to effectively prevent static electricity accumulation and discharge, strengthen electromagnetic shielding, and avoid surface current conduction.

[0004] At present, sulfuric acid hard anodizing is commonly used to grow an insulating coating on the surface of aluminum optical components to increase their service life. However, this method has disadvantages: on the one hand, sulfur will weaken the optical properties, corrosion resistance and thermal stability of the film layer, thereby reducing the imaging quality, stability and service life of the optical system; on the other hand, the ordinary sulfuric acid hard anodizing method is difficult to ensure the dimensional accuracy of the optical components, thus affecting the reliability and accuracy of the optical system.

[0005] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention

[0006] The purpose of the present disclosure is to provide a method for preparing an insulating coating for an aluminum alloy optical component and an insulating coating for an aluminum alloy optical component, thereby overcoming the problem of poor performance of the insulating coating for an aluminum alloy optical component at least to a certain extent.

[0007] According to a first aspect of the present disclosure, there is provided a method for preparing an insulating coating for an aluminum alloy optical component, comprising: pre-treating the aluminum alloy optical component to be treated to obtain a clean aluminum alloy component; placing the clean aluminum alloy component in an anodizing electrolyte, and subjecting the clean aluminum alloy component to an oxidative electrolytic treatment to form an intermediate insulating coating on the surface of the clean aluminum alloy component; wherein the sulfur content of the anodizing electrolyte is zero; placing the aluminum alloy component with the intermediate insulating coating formed on the surface in a target solution for sealing, so as to form a target insulating coating on the surface of the aluminum alloy component; wherein the target solution contains a silane coupling agent and methanol.

[0008] Optionally, the aluminum alloy optical component to be processed is pretreated to obtain a clean aluminum alloy component, including: degreasing the aluminum alloy optical component to be processed to obtain a first intermediate component; chemically polishing the first intermediate component to obtain a second intermediate component; and light-emitting the second intermediate component to obtain a clean aluminum alloy component.

[0009] Optionally, the aluminum alloy optical component to be treated is degreased using a sodium hydroxide solution, the degreasing temperature is 50°C to 75°C, and the degreasing time is 15s to 30s; the first intermediate component is chemically polished using a mixed solution consisting of a phosphoric acid solution and a sulfuric acid solution, the chemical polishing temperature is 90°C to 105°C, and the chemical polishing time is 30s to 40s; the second intermediate component is light-emitting using a nitric acid solution, and the light-emitting time is 10s to 30s.

[0010] Optionally, the oxidation electrolysis treatment includes a first treatment stage, a second treatment stage and a third treatment stage; in the first treatment stage, the voltage is set to 15V to 20V, and the oxidation time is 10min to 15min; in the second treatment stage, the current density is controlled to 0.5A / dm 2 Up to 2.5A / dm 2 , the oxidation time is 10min to 15min, until the voltage increases to 45V to 50V; in the third treatment stage, the voltage is set to 60V to 120V, and the oxidation time is 50min to 70min.

[0011] Optionally, during the oxidation electrolysis treatment, compressed air at 0.5 MPa to 0.85 MPa is introduced, and the cooling temperature is set to -10°C to -5°C.

[0012] Optionally, the anodizing electrolyte comprises 40 g / L to 100 g / L of oxalic acid or oxalate, 10 g / L to 25 g / L of aluminum lactate, 10 g / L to 30 g / L of potassium hydrogen oxalate, and 5 g / L to 10 g / L of an organic acid.

[0013] Optionally, the oxalate is a mixture of one or more of sodium oxalate, potassium oxalate and ammonium oxalate.

[0014] Optionally, the organic acid is formic acid, glycolic acid or a mixture of both.

[0015] Optionally, in the target solution, the content of silane coupling agent is 0.5g / L to 1.5g / L, and the content of methanol is 2g / L to 10g / L; wherein the aluminum alloy component with an intermediate insulating coating formed on the surface is placed in the target solution for sealing for 10min to 15min.

[0016] According to a second aspect of the present disclosure, there is provided an insulating coating for an aluminum alloy optical component, wherein the insulating coating for an aluminum alloy optical component is prepared by using any of the above-mentioned methods for preparing the insulating coating for an aluminum alloy optical component.

[0017] In the scheme of the exemplary embodiment of the present disclosure, the sulfur content in the anodized electrolyte used is zero, thereby reducing the propagation loss of light on the surface and inside the optical component, improving the transmittance and reflectivity, and enhancing the imaging clarity and brightness. In harsh environments such as humidity and corrosive gases, the corrosion resistance is enhanced, the base material is protected, and the service life is extended. In addition, for aluminum alloy optical components working in high-temperature environments, the physical and chemical properties can be kept stable, film problems caused by sulfur can be avoided, and stable operation at high temperatures can be ensured, providing a strong guarantee for the reliable application of optical components in different environments, and promoting the performance improvement of optical systems.

[0018] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The accompanying drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification are used to explain the principles of the present disclosure. Obviously, the accompanying drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without creative work.

[0020] Figure 1 A method for preparing an insulating coating for an aluminum alloy optical component according to an exemplary embodiment of the present disclosure is schematically illustrated.

[0021] Figure 2 A schematic diagram of the cross-sectional morphology of the coating of Example 1 of the present disclosure is shown.

[0022] Figure 3 A schematic diagram of an EDS (Energy Dispersive Spectrometer) layered image of Example 1 of the present disclosure is shown.

[0023] Figure 4 The element distribution diagram of Example 1 of the present disclosure is shown. A represents the microscopic distribution diagram of the Al element; B represents the microscopic distribution diagram of the C element; C represents the microscopic distribution diagram of the O element; D represents the microscopic distribution diagram of the Si element; E represents the microscopic distribution diagram of the Sr element; and F represents the microscopic distribution diagram of the Ca element. DETAILED DESCRIPTION

[0024] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as being limited to the examples set forth herein; on the contrary, these embodiments are provided so that the present disclosure will be more comprehensive and complete, and the concepts of the example embodiments are fully conveyed to those skilled in the art. The described features, structures, or characteristics may be combined in any suitable manner in one or more embodiments. In the following description, many specific details are provided to provide a full understanding of the embodiments of the present disclosure. However, those skilled in the art will appreciate that the technical solutions of the present disclosure may be practiced while omitting one or more of the specific details, or other methods, processes, steps, etc. may be adopted. In other cases, known technical solutions are not shown or described in detail to avoid obscuring various aspects of the present disclosure.

[0025] In addition, the accompanying drawings are only schematic illustrations of the present disclosure and are not necessarily drawn to scale. The same reference numerals in the figures represent the same or similar parts, and thus their repeated descriptions will be omitted. The flowcharts shown in the accompanying drawings are only exemplary illustrations and do not necessarily include all the steps. For example, some steps can also be decomposed, while some steps can be combined or partially combined, so the actual execution order may change according to actual conditions. In addition, all the terms "first", "second", "third", etc. below are only for the purpose of distinction and should not be used as limitations of the present disclosure.

[0026] The solution of the embodiment of the present disclosure can be applicable to aluminum alloys such as 5082, 5183, 6061, and 7075.

[0027] Figure 1 The method for preparing an insulating coating for an aluminum alloy optical component according to an exemplary embodiment of the present disclosure is schematically shown. Figure 1 The method for preparing the insulating coating for the aluminum alloy optical component according to the embodiment of the present disclosure may include the following steps:

[0028] S12. Pre-treating the aluminum alloy optical component to be processed to obtain a clean aluminum alloy component.

[0029] In an exemplary embodiment of the present disclosure, the pretreatment may include a plurality of treatment processes such as a degreasing treatment, a chemical polishing treatment, and a light emitting treatment.

[0030] First, the aluminum alloy optical component to be processed can be degreased to obtain a first intermediate component. Specifically, the aluminum alloy optical component to be processed can be degreased using a sodium hydroxide solution, the degreasing temperature is 50° C. to 75° C., and the degreasing time is 15s to 30s. The content of sodium hydroxide in the sodium hydroxide solution is 45g / L to 60g / L.

[0031] Next, the first intermediate component can be chemically polished to obtain a second intermediate component. Specifically, the first intermediate component can be chemically polished using a mixed solution consisting of a phosphoric acid solution and a sulfuric acid solution, the chemical polishing temperature is 90° C. to 105° C., and the chemical polishing time is 30 s to 40 s. In the mixed solution, the weight percentage of the phosphoric acid solution is, for example, 75 wt % to 80 wt %, and the weight percentage of the sulfuric acid solution is, for example, 20 wt % to 25 wt %.

[0032] Then, the second intermediate component can be subjected to a light treatment to obtain a clean aluminum alloy component. Specifically, the second intermediate component can be subjected to a light treatment using a nitric acid solution at room temperature for 10 to 30 seconds.

[0033] It can be understood that after the above-mentioned pretreatment and cleaning and drying, a clean aluminum alloy component is obtained.

[0034] S14. Place the clean aluminum alloy component in an anodizing electrolyte, and form an intermediate insulating coating on the surface of the clean aluminum alloy component through an oxidative electrolysis treatment; wherein the sulfur content of the anodizing electrolyte is zero.

[0035] In an exemplary embodiment of the present disclosure, the anodizing electrolyte may include 40 g / L to 100 g / L of oxalic acid or oxalate, 10 g / L to 25 g / L of aluminum lactate, 10 g / L to 30 g / L of potassium hydrogen oxalate, and 5 g / L to 10 g / L of an organic acid. Specifically, the oxalate is a mixture of one or more of sodium oxalate, potassium oxalate, and ammonium oxalate, and the organic acid is a mixture of one or two of formic acid and glycolic acid.

[0036] On the one hand, by adding potassium hydrogen oxalate to the anodizing electrolyte, the growth rate of the oxide film can be adjusted, the oxide film can be made to form a dense structure, the hardness can be increased, the friction and collision can be resisted, and the penetration of corrosive ions can be prevented, thereby protecting the aluminum optical components and extending the service life. At the same time, it can make the surface of the oxide film smooth and clean, increase the light transmittance and reflectivity, reduce light scattering and absorption, and improve the imaging quality of the optical system.

[0037] On the other hand, by adding aluminum lactate to the anodizing electrolyte, the pH and conductivity of the electrolyte can be adjusted, the dispersion of ions in the electrolyte can be promoted, the anodizing reaction can be carried out evenly, and at the same time, the oxide film grains can be refined, making the oxide film structure denser, improving the hardness, wear resistance and corrosion resistance of the oxide film, and extending the life of aluminum products.

[0038] In the embodiment of adding glycolic acid to the anodizing electrolyte, the pH value of the electrolyte can be stabilized, the conductivity can be improved, and a complex can be formed with aluminum ions to guide the aluminum ions to be uniformly deposited in the oxide film, so that the structure of the oxide film is regular and dense, and the surface flatness is improved. As a result, the optical transmittance of the oxide film is enhanced, the imaging quality of the optical system is improved, and the resistance to corrosive media is improved, and the degradation of optical performance caused by corrosion is reduced, providing a better surface treatment solution for applications such as optical components, extending their service life, and having important practical application value.

[0039] Through the above-mentioned electrolyte component configuration, the sulfur content of the oxide layer is achieved to be zero, thereby reducing the propagation loss of light on the surface and inside of the optical component, improving the transmittance and reflectivity, and improving the imaging clarity and brightness. In addition, in harsh environments such as humidity and corrosive gases, the corrosion resistance is enhanced, the base material is protected, and the service life is extended. In addition, for optical components working in high-temperature environments, the physical and chemical properties can be kept stable, film problems caused by sulfur can be avoided, and stable operation can be ensured at high temperatures, providing a strong guarantee for the reliable application of optical components in different environments and promoting the performance improvement of optical systems.

[0040] The oxidation electrolysis treatment described in the embodiment of the present disclosure may be a staged process. Specifically, the oxidation electrolysis treatment may include a first treatment stage, a second treatment stage, and a third treatment stage.

[0041] In the first treatment stage, a constant voltage mode may be used, with the voltage set to 15 V to 20 V and the oxidation time to 10 min to 15 min.

[0042] In the second treatment stage, the current density was controlled to 0.5A / dm 2 Up to 2.5A / dm 2 , the oxidation time is 10min to 15min, until the voltage rises to 45V to 50V.

[0043] In the third treatment stage, a constant voltage mode may be used, with the voltage set to 60 V to 120 V and the oxidation time to 50 min to 70 min.

[0044] In addition, during the oxidation electrolysis treatment, compressed air of 0.5 MPa to 0.85 MPa may be introduced, and the cooling temperature may be set to -10°C to -5°C.

[0045] It should be noted that, if the time of the above-mentioned degreasing treatment is recorded as T1, the time of the above-mentioned chemical polishing treatment is recorded as T2, and the oxidation time of the above-mentioned third treatment stage is recorded as T3, then the ratio of T3 to (T1+T2) can be controlled at 1:(50-80).

[0046] By adjusting the ratio between degreasing, chemical polishing and coating oxidation time, the generation and dissolution time of the insulating coating can be effectively adjusted, thereby achieving high-precision control of the film layer size and realizing a single-side size change in the range of 0μm to 3μm.

[0047] In addition, through, for example, the above-mentioned staged process, the structure of the insulating oxide layer can be effectively controlled, so that the hard anodized film layer has the characteristics of high bonding strength, low roughness and high hardness, and the surface hardness of aluminum alloy parts can be increased to more than 400HV.

[0048] S16. Placing the aluminum alloy component with an intermediate insulating coating formed on the surface into a target solution for sealing, so as to form a target insulating coating on the surface of the aluminum alloy component; wherein the target solution contains a silane coupling agent and methanol.

[0049] In an exemplary embodiment of the present disclosure, the silane coupling agent may be one or more of KH507, KH792, and KH-602. In the target solution, the content of the silane coupling agent may be 0.5 g / L to 1.5 g / L, and the content of methanol may be 2 g / L to 10 g / L.

[0050] Specifically, the aluminum alloy component with the intermediate insulating coating formed on the surface can be placed in the target solution for sealing for 10 minutes to 15 minutes.

[0051] Next, the aluminum alloy component is taken out, washed with water and dried to obtain the target insulating coating.

[0052] After testing, the single-side size change of aluminum alloy before and after treatment is less than 3μm, and the volume resistivity is greater than 10 14 Ω·cm.

[0053] The preparation scheme of the embodiment of the present disclosure is described below by way of examples.

[0054] Example 1

[0055] Step 1. First, place the 5183 aluminum alloy parts in a 45g / L NaOH solution for degreasing treatment, set the temperature to 75°C, and the time is 15s. Next, chemical polishing is performed in a mixed solution composed of 80wt% H3PO4 and 20wt% H2SO4, the temperature is set to 105°C, and the time is 30s. Then, light treatment is performed in a 25wt% HNO3 solution at room temperature for 30s. Subsequently, the aluminum alloy components after the above pretreatment are ultrasonically cleaned and dried to obtain a flat and clean aluminum alloy substrate.

[0056] Step 2: Place the clean aluminum alloy substrate in an electrolyte consisting of 100 g / L potassium oxalate, 15 g / L aluminum lactate, 10 g / L potassium hydrogen oxalate, and 5 g / L glycolic acid, and introduce 0.85 MPa of clean compressed air. Set the cooling temperature to -5°C. First, set the voltage to 15 V and oxidize for 10 minutes. Then, control the current density to 2.5 A / dm 2 , oxidation for 15 minutes, the voltage reaches 46 V. Then, the voltage is adjusted to 120 V, oxidation for 60 minutes, and an aluminum alloy substrate with a high-precision, sulfur-free insulating oxide layer on the surface is obtained.

[0057] Step three, placing the aluminum alloy substrate with a high-precision, sulfur-free insulating oxide layer on the surface obtained in step two in a mixed solution of 1.5 g / L KH507 and 10 g / L methanol for 15 minutes, taking it out, washing it with water, and then drying it.

[0058] In this embodiment, the ratio of T3 to (T1+T2) is 1:80, the change in the single-side size before and after the aluminum alloy treatment is 3 μm, the sulfur content is 0, and the resistance value is 2.32×10 14 Ω·cm.

[0059] Figure 2 FIG. 1 is a schematic diagram showing the cross-sectional morphology of the coating of Example 1 of the present disclosure. Figure 2 The insulating coating prepared by the present invention has clear layers and no cracks or holes. Figure 3 Shown with Figure 2 Corresponding EDS layered images.

[0060] Figure 4 Schematic diagram of element distribution of Example 1 of the present disclosure is shown. Figure 4 The distribution uniformity of elements in the coating prepared by the preparation scheme of Example 1 of the present disclosure is good.

[0061] Example 2

[0062] Step 1: First, place the 6061 aluminum alloy part in a 45g / L NaOH solution for degreasing treatment, set the temperature to 65°C, and the time is 20s. Next, perform chemical polishing in a mixed solution consisting of 80wt% H3PO4 and 20wt% H2SO4, set the temperature to 105°C, and the time is 40s. Then, perform light treatment in a 25wt% HNO3 solution at room temperature for 20s. Subsequently, the aluminum alloy component after the above pretreatment is ultrasonically cleaned and dried to obtain a flat and clean aluminum alloy substrate.

[0063] Step 2: Place the clean aluminum alloy substrate in an electrolyte consisting of 80g / L sodium oxalate, 10g / L aluminum lactate, 20g / L potassium hydrogen oxalate, and 8g / L formic acid, and introduce 0.65MPa of clean compressed air. Set the cooling temperature to -7°C. First, set the voltage to 15V and oxidize for 10min. Then, control the current density to 1.5A / dm 2 , oxidation for 12 minutes, the voltage reaches 50 V. Then, the voltage is adjusted to 80 V, oxidation for 70 minutes, and an aluminum alloy substrate with a high-precision, sulfur-free insulating oxide layer on the surface is obtained.

[0064] Step three, placing the aluminum alloy substrate with a high-precision, sulfur-free insulating oxide layer on the surface obtained in step two in a mixed solution of 1.5 g / L KH507 and 5 g / L methanol for 15 minutes, taking it out, washing it with water, and then drying it.

[0065] In this embodiment, the ratio of T3 to (T1+T2) is 1:70, the change in the single-side dimension before and after the aluminum alloy treatment is 0 μm, the sulfur content is 0, and the resistance value is 2.43×10 14 Ω·cm.

[0066] Example 3

[0067] Step 1: First, place the 5082 aluminum alloy part in a 45g / L NaOH solution for degreasing treatment, set the temperature to 50°C, and the time is 30s. Next, perform chemical polishing in a mixed solution consisting of 80wt% H3PO4 and 20wt% H2SO4, set the temperature to 90°C, and the time is 30s. Then, perform light treatment in a 25wt% HNO3 solution at room temperature for 10s. Subsequently, the aluminum alloy component after the above pretreatment is ultrasonically cleaned and dried to obtain a flat and clean aluminum alloy substrate.

[0068] Step 2: Place the clean aluminum alloy substrate in an electrolyte consisting of 40g / L oxalic acid, 25g / L aluminum lactate, 30g / L potassium hydrogen oxalate, and 10g / L glycolic acid, and introduce 0.5MPa of clean compressed air. Set the cooling temperature to -10°C. First, set the voltage to 15V and oxidize for 10min. Then, control the current density to 0.5A / dm 2 , oxidized for 10 minutes, and the voltage reached 45 V. Then, the voltage was adjusted to 60 V and oxidized for 50 minutes to obtain an aluminum alloy substrate with a high-precision, sulfur-free insulating oxide layer on the surface.

[0069] Step three, placing the aluminum alloy substrate with a high-precision, sulfur-free insulating oxide layer on the surface obtained in step two in a mixed solution of 0.5 g / L KH507 and 2 g / L methanol for 10 minutes, taking it out, washing it with water, and then drying it.

[0070] In this embodiment, the ratio of T3 to (T1+T2) is 1:50, the change in the single-side dimension before and after the aluminum alloy treatment is 1.5 μm, the sulfur content is 0, and the resistance value is 1.6×10 14 Ω·cm.

[0071] Example 4

[0072] Step 1: First, place the 7075 aluminum alloy parts in a 45g / L NaOH solution for degreasing treatment, set the temperature to 75°C, and the time is 15s. Next, chemical polishing is performed in a mixed solution composed of 80wt% H3PO4 and 20wt% H2SO4, the temperature is set to 105°C, and the time is 30s. Then, light treatment is performed in a 25wt% HNO3 solution at room temperature for 30s. Subsequently, the aluminum alloy components after the above pretreatment are ultrasonically cleaned and dried to obtain a flat and clean aluminum alloy substrate.

[0073] Step 2: Place the clean aluminum alloy substrate in an electrolyte consisting of 90 g / L ammonium oxalate, 15 g / L aluminum lactate, 8 g / L potassium hydrogen oxalate, and 8 g / L glycolic acid, and introduce 0.65 MPa of clean compressed air. Set the cooling temperature to -5°C. First, set the voltage to 20 V and oxidize for 15 minutes. Then, control the current density to 2.5 A / dm 2 , oxidized for 15 minutes, and the voltage reached 42 V. Then, the voltage was adjusted to 90 V and oxidized for 50 minutes to obtain an aluminum alloy substrate with a high-precision, sulfur-free insulating oxide layer on the surface.

[0074] Step three, placing the aluminum alloy substrate with a high-precision, sulfur-free insulating oxide layer on the surface obtained in step two in a mixed solution of 1.5 g / L KH507 and 10 g / L methanol for 15 minutes, taking it out, washing it with water, and then drying it.

[0075] In this embodiment, the ratio of T3 to (T1+T2) is 1:66.67, the change in the single-side dimension before and after the aluminum alloy treatment is 2.5 μm, the sulfur content is 0, and the resistance value is 3.55×10 14 Ω·cm.

[0076] The aluminum alloy components prepared in the above Examples 1 to 4 were tested, and the test results are shown in Table 1:

[0077] Table 1

[0078]

[0079] It can be seen that by adopting the preparation method of the embodiment of the present disclosure, the effect of smaller unilateral size change and better hardness effect can be obtained.

[0080] Furthermore, the embodiments of the present disclosure also provide an insulating coating for an aluminum alloy optical component, and the insulating coating for an aluminum alloy optical component is prepared by the above-mentioned method for preparing the insulating coating for an aluminum alloy optical component.

[0081] It should be noted that although the steps of the method in the present disclosure are described in a specific order in the drawings, this does not require or imply that the steps must be performed in this specific order, or that all the steps shown must be performed to achieve the desired results. Additionally or alternatively, some steps may be omitted, multiple steps may be combined into one step, and / or one step may be decomposed into multiple steps, etc.

[0082] In addition, the above-mentioned figures are only schematic illustrations of the processes included in the method according to the exemplary embodiments of the present disclosure, and are not intended to be limiting. It is easy to understand that the processes shown in the above-mentioned figures do not indicate or limit the time sequence of these processes. In addition, it is also easy to understand that these processes can be performed synchronously or asynchronously, for example, in multiple modules.

[0083] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing what is disclosed herein. This application is intended to cover any variations, uses, or adaptations of the present disclosure that follow the general principles of the present disclosure and include common knowledge or customary technical means in the art that are not disclosed in the present disclosure. The specification and embodiments are to be considered merely as exemplary, and the true scope and spirit of the present disclosure are indicated by the claims.

[0084] It should be understood that the present disclosure is not limited to the exact structures that have been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present disclosure is limited only by the appended claims.

Claims

1. A method for preparing an insulating coating for an aluminum alloy optical component, characterized in that: include: Pre-treating the aluminum alloy optical components to be processed to obtain clean aluminum alloy components; Placing the clean aluminum alloy component in an anodic oxidation electrolyte, and subjecting the component to an oxidation electrolytic treatment to form an intermediate insulating coating on the surface of the clean aluminum alloy component; wherein the sulfur content of the anodic oxidation electrolyte is zero; The aluminum alloy component with the intermediate insulating coating formed on the surface is placed in a target solution for sealing, so as to form a target insulating coating on the surface of the aluminum alloy component; wherein the target solution contains a silane coupling agent and methanol.

2. The preparation method according to claim 1, characterized in that: Pre-treat the aluminum alloy optical components to obtain clean aluminum alloy components, including: Degreasing the aluminum alloy optical component to be processed to obtain a first intermediate component; Performing chemical polishing on the first intermediate component to obtain a second intermediate component; The second intermediate component is subjected to a light treatment to obtain a clean aluminum alloy component.

3. The preparation method according to claim 2, characterized in that: Degreasing the aluminum alloy optical component to be processed by using a sodium hydroxide solution, the degreasing temperature is 50° C. to 75° C., and the degreasing time is 15s to 30s; The first intermediate component is subjected to chemical polishing treatment using a mixed solution consisting of a phosphoric acid solution and a sulfuric acid solution, the chemical polishing temperature is 90° C. to 105° C., and the chemical polishing time is 30s to 40s; The second intermediate component is subjected to light emitting treatment using a nitric acid solution, and the light emitting treatment time is 10s to 30s.

4. The preparation method according to claim 1, characterized in that: The oxidation electrolysis treatment includes a first treatment stage, a second treatment stage and a third treatment stage; In the first treatment stage, the voltage is set to 15V to 20V and the oxidation time is set to 10min to 15min; In the second treatment stage, the current density is controlled to be 0.5A / dm 2 Up to 2.5A / dm 2 , the oxidation time is 10min to 15min, until the voltage increases to 45V to 50V; In the third treatment stage, the voltage is set to 60V to 120V, and the oxidation time is set to 50min to 70min.

5. The preparation method according to claim 1 or 4, characterized in that: During the oxidation electrolysis treatment, compressed air at 0.5 MPa to 0.85 MPa was introduced, and the cooling temperature was set to -10°C to -5°C.

6. The preparation method according to claim 1, characterized in that: The anodizing electrolyte comprises 40 g / L to 100 g / L of oxalic acid or oxalate, 10 g / L to 25 g / L of aluminum lactate, 10 g / L to 30 g / L of potassium hydrogen oxalate, and 5 g / L to 10 g / L of an organic acid.

7. The preparation method according to claim 6, characterized in that: The oxalate is a mixture of one or more of sodium oxalate, potassium oxalate and ammonium oxalate.

8. The preparation method according to claim 6, characterized in that: The organic acid is formic acid, glycolic acid or a mixture of both.

9. The preparation method according to claim 1, characterized in that: In the target solution, the content of the silane coupling agent is 0.5 g / L to 1.5 g / L, and the content of the methanol is 2 g / L to 10 g / L; The aluminum alloy component with the intermediate insulating coating formed on the surface is placed in the target solution for sealing for 10 minutes to 15 minutes.

10. An insulating coating for an aluminum alloy optical component, characterized in that: The insulating coating for an aluminum alloy optical component is prepared by the method for preparing the insulating coating for an aluminum alloy optical component according to any one of claims 1 to 9.